Managing tropical Sal forests (Shorea robusta) in Nepal in short rotations: findings of a 12-year long research - Acharya, K.P.; Tamrakar, P.R.; Gautam, G.; Regmi, R.; Adhikari, A.; Acharya, B. (Banko Janakari, 2017)
Abstract available on the PDF Banko Janakari Vol.12(1) 2002: 71-75